Pregnancy in the Setting of Asymptomatic Non-Cirrhotic Chronic Portal Vein Thrombosis Complicated by Pre-Eclampsia - Işık Üstüner; Remzi Adnan Akdoğan; Emine Seda Güvendağ Güven; Figen Kır Şahin; Şenol Şentürk; Elif Akdoğan; Filiz Taşçı (Case Reports in Obstetrics and Gynecology)
Portal vein thrombosis (PVT) can be chronic or acute in nature; it is characterized by a thrombus formation in the main portal vein and/or its right or left branches. Herein, we present a 36-year-old woman with asymptomatic noncirrhotic chronic PVT who developed preeclampsia in the later stage of pregnancy. This report will emphasize the clinical differential diagnosis, outcome, and management of pregnancies complicated by noncirrhotic PVT.